Protective Effect of Hypothermia in a Blunt Thoracic Trauma and Hemorrhagic Shock Model - Ulger, Hüseyin; Deniz, Turgut; Comu, Faruk; Agalar, Canan; Kisa, Ucler; Agalar, Fatih (The Thoracic and Cardiovascular Surgeon, 2014)
Background The aim of this study was to investigate the effect of volume-controlled hemorrhage and hypothermia on rats with blunt chest trauma, evaluating bacterial translocation (BT), lung tissue malondialdehyde (MDA), nitric oxide (NO) levels, and erythrocyte deformability (ED).Methods In our study, 10 animals each were included in 6 groups. Groups were as follows: a group with blunt chest trauma only (Group T), a group with hemorrhage only (Group H), a normothermic group with comorbidity of trauma and hemorrhage (Group NT), a mild hypothermic group with trauma and hemorrhage (Group MH), a moderate hypothermic group with trauma and hemorrhage (Group MoH), and a control group (Group C). Sodium pentobarbital (50 mg/kg, intraperitoneally) anesthesia was administered. Thoracic trauma was generated using kinetic energy at the middle of the chest (2.45 J). Stage 3 hemorrhagic shock was initiated. After 24 hours, the rats were killed and red blood cell deformability, BT development in the liver, spleen, and mesenteric lymph nodes, and NO and MDA levels in lung tissue, kept at −80°C, were measured.Results In Groups MH and MoH, there was no difference in ED values, though they were lower than those in Group NT (p < 0.05). BT was more prevalent in Group NT than in the other groups. In Group NT, the growth of BT was greater than in other groups (p < 0.05). The level of NO in Group H was higher than in the control group (p < 0.05). In Group MoH, the level of MDA was lower than in Group MH (p < 0.05).Conclusion Hypothermia seems to demonstrate protective effects on ED and BT by reducing oxidative stress. The protective effects of therapeutic hypothermia on ED may be due to the effect of reducing NO and/or MDA. There was no difference in effect between mild and moderate hypothermia in terms of the formation of ED and BT.
Keywords: chest; trauma; experimental; hypothermia/circulatory arrest; infection; shock